Estimating Firm-Level Effective Marginal Tax Rates and the User Cost of Capital in New Zealand - Richard Fabling; Norman Gemmell; Richard Kneller; Lynda Sanderson (New Zealand Government, The Treasury, 2013)
Effective marginal tax rates (EMTRs) can be very different from the statutory rate and vary across firms, reflecting such factors as the extent and nature of taxable deductions (losses, depreciation), asset and ownership structures, and debt/equity financing. We estimate firm-specific EMTRs and related user cost of capital (UCC) measures allowing for shareholder-level taxation using data for 1999/2000-2010/11 from the Longitudinal Business Database. Examining distributions of various UCC measures we find substantial firm-level heterogeneity, systematic changes as a result of tax reforms between 2004 and 2012, and systematic differences between foreign-owned and domestically-owned firms. Choices among alternative UCC measures make a difference to interpretations.
Keywords: D22; G30; H25; 330; User cost of capital; tax reform; EMTR; New Zealand; Unternehmensbesteuerung; Shareholder Value; Kapitalkosten; Kapitalertragsteuer; Steuerreform; Steuerwirkung; Neuseeland